Family Guide to the National Insurance Scheme ([London] : His Majesty's Stationery Office, 1948)
1948 1948 1940s 32 pages : illustrations ment to 9s. a week for 20 per cent disablement. For an assessment of less than 20 per cent a gratuity will be paid, ranging from £15 to £150. It is not necessary for Injury Benefit to be paid for 26 weeks before you can get Disablement Benefit. Disablement Benefit can be increased for various reasons: (а) If you have to go into hospital for treatment, you will get the benefit at the full rate of 45s. a week even if you are not 100 per cent disabled, together with Dependant's Allowances if you are entitled to them. (b) If you are 100 per cent disabled and need someone to took after you, a Constant Attendance Allowance up to 20s. a week may be paid. In special cases this may be increased up to 40s. a week. (c) If you are permanently unfit for work an Unemployability Supplement of 20s. a week may be paid, with allowances for dependants. You can draw Unemployability Supplement and Constant Attendance Allowance at the same time. [Picture] ... accident arising in the course of employment ... 29 345/3/2/10